3D Vision Provides Shorter Operative Time and More Accurate Intraoperative Surgical Performance in Laparoscopic Hiatal Hernia Repair Compared With 2D Vision: A Case-Control Analysis. (April 2017) - Leon, Piera; Rivellini, Roberta; Giudici, Fabiola; Sciuto, Antonio; Pirozzi, Felice; Corcione, Francesco
Background . The aim of this study is to evaluate if 3-dimensional high-definition (3D) vision in laparoscopy can prompt advantages over conventional 2D high-definition vision in hiatal hernia (HH) repair. Study design . Between September 2012 and September 2015, we randomized 36 patients affected by symptomatic HH to undergo surgery; 17 patients underwent 2D laparoscopic HH repair, whereas 19 patients underwent the same operation in 3D vision. Results . No conversion to open surgery occurred. Overall operative time was significantly reduced in the 3D laparoscopic group compared with the 2D one (69.9 vs 90.1 minutes, P = .006). Operative time to perform laparoscopic crura closure did not differ significantly between the 2 groups. We observed a tendency to a faster crura closure in the 3D group in the subgroup of patients with mesh positioning (7.5 vs 8.9 minutes, P = .09). Nissen fundoplication was faster in the 3D group without mesh positioning ( P = .07). Conclusions . 3D vision in laparoscopic HH repair helps surgeon's visualization and seems to lead to operative time reduction. Advantages can result from the enhanced spatial perception of narrow spaces. Less operative time and more accurate surgery translate to benefit for patients and cost savings, compensating the high costs of the 3D technology. However, more data from larger series are needed to firmly assess the advantages of 3D over 2D vision in laparoscopic HH repair.